Implementasi Self Healing Untuk Mengatasi Kecemasan pada Pasien Gagal Ginjal Kronik Yang Menjalani Hemodialisa di Rs Permata Medika Semarang - Dwi Nur Aini; Maulidta Karunianingtyas Wirawati; Menik Kustriyani; Arifianto Arifianto; Mariyati Mariyati; Mohammad Arifin Noor; Desi Ramadhani; Muhammad Azkanni’am (Pusat Riset dan Inovasi Nasional, 2023)
HD room nurses are health workers who play an active role in managing nursing care starting from assessment, both physically and psychologically. Determine nursing problems that arise in patients based on the results of the assessment, determine interventions, carry out implementation according to the plans that have been determined and evaluate the actions / implementations that have been carried out. In accordance with the problems experienced by these partners, the efforts made include implementing self-healing in chronic kidney failure patients undergoing hemodialysis therapy who experience anxiety. The specific target of this PKM activity is to teach self-healing therapy in the prevention and treatment of anxiety, especially in chronic kidney failure patients undergoing hemodialysis therapy at Permata Medika Hospital, Semarang. Teaching chronic kidney failure patients undergoing hemodialysis therapy how to do self-healing. Demonstration of self-healing therapy according to SOP. The result of this service activity is that the level of knowledge of chronic kidney failure patients undergoing hemodialysis therapy at Permata Medika Hospital in Semarang increases after being given material on self-healing management with five finger hypnosis, besides that the patient is able to carry out a simulation on how to reduce anxiety with five finger hypnosis.